Credit Risk Management Practices and Loan Performance of Commercial Banks in Uganda - Agaba, Francis; Tamwesigire, Caleb; Eton, Marus (Business Perspective Review, 2022)
Purpose: The study examined the relationship between Credit Risk Management Practices and Loan Performance of Commercial Banks in Mbarara City. The study covered 19 commercial banks. Method: A correlational design was used to establish the relationship between different credit risk management practices and Loan Performance in selected commercial banks in the city. The study used a structured questionnaire to collect numerical data from the credit staff and management of 19 commercial banks. Correlation and regression tests to analyze the relationships and effects of Credit risk management and Loan Performance of commercial banks in Mbarara city Findings: The study found a significant relationship between credit risk identification and loan performance; credit risk assessment and loan performance; credit risk monitoring and loan performance; and credit risk control and loan performance. The study also found that some commercial banks did not have experts to accurately predict credit risks nor evaluate the consequences of the decisions taken by loan officers. Implication: Banks should source experts who can analyze and predict risks and evaluate their consequences on the bank. The bank should adopt the tool of 5cs of credit management, with this it will develop a good loan book that shall lead to good loan performance. Limitations: We still don't know clients' perceptions of the different credit risk management practices. Therefore, a qualitative study to assess clients' perception of the credit management practices in commercial banks should be conducted.